CD18 controls the development and activation of monocyte-to-macrophage axis during chronic schistosomiasis - Souza, Camila O. S.; Elias-Oliveira, Jefferson; Pastore, Marcella R.; Fontanari, Caroline; Rodrigues, Vanessa F.; Rodriguez, Vanderlei; Gardinassi, Luiz G.; Faccioli, Lúcia H. (Frontiers in Immunology, 2022)
Schistosomiasis is a neglected tropical disease caused by worms of the genus Schistosoma spp. The progression of disease results in intense tissue fibrosis and high mortality rate. After egg deposition by adult worms, the inflammatory response is characterized by the robust activation of type 2 immunity. Monocytes and macrophages play critical roles during schistosomiasis. Inflammatory Ly6Chigh monocytes are recruited from the blood to inflammatory foci and differentiate into alternatively activated macrophages (AAMs), which promote tissue repair. The common chain of β2-integrins (CD18) regulates monocytopoiesis and mediates resistance to experimental schistosomiasis. There is still limited knowledge about mechanisms controlled by CD18 that impact monocyte development and effector cells such as macrophages during schistosomiasis. Here, we show that CD18low mice chronically infected with S. mansoni display monocyte progenitors with reduced proliferative capacity, resulting in the accumulation of the progenitor cell denominated proliferating-monocyte (pMo). Consequently, inflammatory Ly6Chigh and patrolling Ly6Clow monocytes are reduced in the bone marrow and blood. Mechanistically, low CD18 expression decreases Irf8 gene expression in pMo progenitor cells, whose encoded transcription factor regulates CSFR1 (CD115) expression on the cell surface. Furthermore, low CD18 expression affects the accumulation of inflammatory Ly6Chigh CD11b+ monocytes in the liver while the adoptive transference of these cells to infected-CD18low mice reduced the inflammatory infiltrate and fibrosis in the liver. Importantly, expression of Il4, Chil3l3 and Arg1 was downregulated, CD206+PD-L2+ AAMs were reduced and there were lower levels of IL-10 in the of liver CD18low mice chronically infected with S. mansoni. Overall, these findings suggest that CD18 controls the IRF8-CD115 axis on pMo progenitor cells, affecting their proliferation and maturation of monocytes. At the same time, CD18 is crucial for the appropriate polarization and function of AAMs and tissue repair during chronic schistosomiasis.